2018
DOI: 10.1371/journal.pbio.2004426
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity-based boosting of neuroepithelial nucleokinesis via indirect energy transfer from mother to daughter

Abstract: Neural progenitor cells (NPCs), which are apicobasally elongated and densely packed in the developing brain, systematically move their nuclei/somata in a cell cycle–dependent manner, called interkinetic nuclear migration (IKNM): apical during G2 and basal during G1. Although intracellular molecular mechanisms of individual IKNM have been explored, how heterogeneous IKNMs are collectively coordinated is unknown. Our quantitative cell-biological and in silico analyses revealed that tissue elasticity mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 60 publications
7
30
0
Order By: Relevance
“…We compared the frequency of occurrence of such identified mitosis events per unit time period (60 min) and per unit apical-surface area (60 μm × 60 μm). As shown in Figure 3a, the frequency was 7.59 ± 1.14 in 3D culture (obtained from three separate fields of an E13 cerebral wall), reproducing the results obtained in previous studies that used E13 cerebral wall cultures (Okamoto et al, 2013;Shinoda et al, 2018). As shown in Figure 3b, the frequency of mitosis occurrence was 8.00 ± 1.00 in in utero 2PM (three separate fields from two independent E13 embryos), and no statistically significant difference was obtained between these two groups (p = .7, exact Wilcoxon rank-sum test; Figure 3c).…”
Section: Comparison Of Apical Cytogenesis Between Slice Culture Andsupporting
confidence: 89%
See 3 more Smart Citations
“…We compared the frequency of occurrence of such identified mitosis events per unit time period (60 min) and per unit apical-surface area (60 μm × 60 μm). As shown in Figure 3a, the frequency was 7.59 ± 1.14 in 3D culture (obtained from three separate fields of an E13 cerebral wall), reproducing the results obtained in previous studies that used E13 cerebral wall cultures (Okamoto et al, 2013;Shinoda et al, 2018). As shown in Figure 3b, the frequency of mitosis occurrence was 8.00 ± 1.00 in in utero 2PM (three separate fields from two independent E13 embryos), and no statistically significant difference was obtained between these two groups (p = .7, exact Wilcoxon rank-sum test; Figure 3c).…”
Section: Comparison Of Apical Cytogenesis Between Slice Culture Andsupporting
confidence: 89%
“…When IUE-labeled embryos were subjected to intravital 2PM, finding ideally labeled NPCs in the VZ was difficult, and excessive searching of appropriate fields damaged the embryos. Previous studies revealed that mitosis and IKNM in NPCs visualized in slices prepared from H2B-mCherry mouse embryos (Okamoto et al, 2013;Shinoda et al, 2018) were equivalent to those observed during sporadic visualization of NPCs (Konno et al, 2008;Miyata et al, 2001;Okamoto et al, 2013). Technically, monitoring at 5 μm from the apical surface is useful for capturing (a) apical-ward migration of a G2-phase NPC's nucleus, (b) mitosis of that NPC, and (c) basal-ward IKNM of G1-phase daughter cells generated by that NPC (Okamoto et al, 2013;Shinoda et al, 2018).…”
Section: In Utero Observation Of Npc Dynamics Near the Apical Surfamentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies have demonstrated that the apical surface of the ventricular zone undergoes actomyosin-dependent contraction, further crowding the apical surface with elastic processes of surrounding progenitor cells. These dense processes exert a centripetal force on the dividing nuclei, thereby enhancing their dorsal displacement (Shinoda et al, 2018) (Figure 4). Recent studies have also demonstrated that apical-to-basal migration stops at the boundary of the ventricular zone and the SVZ by the physical fence made by differentiated SVZ neurons (Watanabe et al, 2018) (Figure 4).…”
Section: Mechanical Properties Of the Extracellular Environmentmentioning
confidence: 99%